Factors affecting the recruitment of Amphibalanus improvisus and Dreissena polymorpha in a highly eutrophic brackish bay. (5th January 2017) - Oganjan, Katarina; Lauringson, Velda; Kotta, Jonne; Rostin, Liis; Martin, Georg
Abstract: Species invasions are modifying ecosystems worldwide. Coexistence of invasive species of no common evolutionary history in their new ranges enables the study of ecological rules shaping novel communities at their initial stages. In oligohaline parts of the Baltic Sea, the most dominant and widespread epifaunal suspension feeders are invasive mussels Dreissena polymorpha and cirripeds Amphibalanus improvisus . This study experimentally evaluated recruitment and microhabitat use in response to environmental forcing in these two species in a eutrophic bay. Recruitment was structured by different microhabitat exploitation patterns coupled with both individual and interactive effects of several environmental gradients. Despite functional similarity, the importance of environmental gradients differed between these species: mussel recruitment was best explained by temperature while barnacle recruitment was best explained by wave exposure. Zebra mussels were more fastidious about surface orientation than barnacles. The preferred orientations also differed between species, as mussels strongly preferred horizontal surfaces, while barnacles were more abundant on vertical surfaces. Increase in one species also predicted well the abundance of the other, especially for barnacles, as mussel abundance was the best predictor of barnacle abundance over all the other factors. The extent of microhabitat segregation correlated weakly over the studied range of the most important environmental gradients. The study shows that coexistence of functionally similar non-native D. polymorpha and A. improvisus in their sympatric range is likely determined by complex interactions between these species, their different microhabitat exploitation patterns, environmental limitations and optima. Highlights: Knowledge of benthic suspension feeder recruitment is essential for management. Artificial substrate was used to estimate recruitment of two introduced species. Reciprocal facilitation was important for zebra mussel and bay barnacle recruitment. Recruitment is subject to microhabitat segregation based on surface orientation.